Privatization Processes in Banking - Motives and Models - Ristić, Života (Panoeconomicus, 2006)
The paper consists of three methodologically and causally connected thematic parts: the first part deals with crucial motives and models of the privatization processes in the USA and EU with a particular analytical focus on the Herfindahl-Hirschman doctrine of the collective domination index, as well as on the essence of merger-acquisition and take-over models. The second thematic part of the paper, as a logical continuation of the first one represents a brief comparative analysis of the motives and models implemented in bank privatization in the south-eastern European countries with particular focus on identifying interests of foreign investors, an optimal volume and price of the investment, and assessment of finalized privatizations in those countries. The final part of the paper theoretically and practically stems from the first and the second part, in that way making an interdependent and a compatible thematic whole with them, presents qualitative and quantitative aspects of analyzing finalized privatization and/or sale-purchase of Serbian banks with particular focus on IPO and IPOPLUS as the prevailing models of future sale-purchase in privatizing Serbian banks. Key words: Bank privatization processes, Crucial motives and models, Compatibility, Causality and comparability. JEL: G21, G28.